Sighah Al-Amr dalam Al-Qur’an Surah Maryam, Al-Anbiya’, dan Al-Mu’minun / Shigah Al-Amr in the Holy Qur'an Surah Maryam, Al- Anbiya, and Al Mu'minun - Abdul Gani (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2020)
هذا البحث يتحدث عن صيغ الأمر ومعانيها في القرآن الكريم (دراسة تحليلية بلاغية في سورة مريم وسورة الأنبياء وسورة المؤمنون). وهذا البحث يهدف إلى معرفة صيغ الأمر في القرآن الكريم في سورة مريم وسورة الأنبياء وسورة المؤمنون، ومعرفة معان صيغ الأمر وقيمها في القرآن الكريم في سورة مريم وسورة الأنبياء وسورة المؤمنون. والمنهج لهذا البحث هو منهج مكتبي الذي به قام الباحث بالتحليل المعاني التي تعتبر من نصوص القرآن التي تحتوي على صيغ الأمر. وبعد ما قام الباحث بتحليل ثلاث سور مريم والأنبياء والمؤمنون. فحصل الباحث على أن صيغ الأمر أمر حقيقي، ولكن إذا ارتبط بين النصوص والمقامات فحصل الباحث على أنها تحتوي على معاني متعددة من نحو (الدعاء) و(الوعيد) و(اللوم) و(الذم) و(التمني) وفي معاني آخر التي تعتبر بمقتضى الحال.الكلمات المفتاحية: صيغ الأمر في القرآن الكريم (دراسة تحليلية بلاغية)Abstract This research discuss about the form of orders and the meanings in holi Qur’an surah Maryam, al-Anbiya’, and al-Mu’minun with balagah analysis. As for purpose in this research namely to analyze the form of orders in holi Qur’an surah Maryam, al-Anbiya’, and al-Mu’minun, and then explain the meaning of form of orders with the values in this surah. This research is a library research with using an analysis discourse approach that’s examine the meanings implied in holi Qur’an which contain the command value. After the researcher conducted an analysis of the three surah, get the form of orders which are in command but if correlated between the text and context it turn out the commond his multiple meanings such as prayer, threats, ridicule. Insults, hopes, and other meaning with are determined by the suitability of an expression with situation and condition surrounding it.